He Whakapapa Tōu, He Tuakiri Anō Tōu: The Importance of Whakapapa to an Urban Māori Identity - Smith, Wahineata (Auckland University of Technology, 2012)
The main purpose of this thesis is to determine whether whakapapa is still an important facet of Māori culture for urban Māori today. The effect of mass migration to urban centres has had a major impact on Māori culture and in the decline of the language and cultural knowledge. The terms whakapapa and tuakiri are synonymous in a traditional Māori setting. In fact, the term tuakiri has acquired a contemporary meaning equivalent to identity. Furthermore, there is a need to determine if the lack of whakapapa knowledge has a direct impact on an urban Māori identity. Due to urbanisation and the growing number of Māori moving away from their papa kāinga, there are a multitude of people who have become disenfranshised from their Māoritanga, from their whakapapa and from their tribal lands. Thus the genesis of this research topic; what significance has whakapapa in a contemporary setting to the the identity of urban Māori? The notions of ahikā and rāwaho are closely examined to show the need for a continuing relationship between the two, and the importance of acquiring knowledge of whakapapa to inform one’s identity. Nō mai rā anō he āhuatanga whakahirahira te whakapapa ki te Māori, he tirohanga te tuhinga nei ki te whakahirahiratanga o te whakapapa ki te tuakiri o Ngāi Māori e noho ā-tāone ana i ēnei rā. I ēnei rā nei, kāore i ārikarika ngā tāngata kāore e mōhio ana ko wai rātou, nō whea hoki rātou, arā, tō rātou whakapapa ake. I roto hoki i te tuhinga nei ētehi kōrero akiaki mō te whanaungatanga i waenganui i te ahikā me te rāwaho kia māmā ai te hokihoki atu ki te papa kāinga, kaua me te whakamā, me te āwangawanga rānei. He tirohanga hoki ki te whakahirahiratanga o te ako whakapapa ki te whakapuaki i te tuakiri o te tangata Māori.
Keywords: Whakapapa; Tuakiri; Kaupapa Māori; Io; Rāwaho; Ahikā